1998
DOI: 10.1021/js970372e
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein (P-gp) Mediated Efflux in Caco-2 Cell Monolayers: The Influence of Culturing Conditions and Drug Exposure on P-gp Expression Levels

Abstract: The influence of cell culture conditions and previous drug exposure on P-glycoprotein (P-gp) expression levels in Caco-2 cells was determined. In this study, the expression of P-gp is demonstrated (i) visually by confocal laser scanning microscopy (CLSM), (ii) functionally by transport studies with substrates of the efflux pump, and (iii) quantitatively by flow cytometry (FCM) analysis using specific monoclonal antibodies (anti P-gp MRK 16 as an external antibody and P-GlycoCheck C219 as an internal antibody).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
118
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(126 citation statements)
references
References 19 publications
8
118
0
Order By: Relevance
“…1A). Next, we asked whether shear stress increased the expression of an endogenous PXR target gene MDR1, which is a known PXR target encoding p-glycoprotein or ATP-binding cassette B1 (ABCB1), a transporter responsible for drug efflux (12,13). Quantitative reverse-transcriptase PCR (qRT-PCR) showed that MDR1 expression was induced by LSS, but not OSS, in human umbilical vein ECs (HUVECs) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1A). Next, we asked whether shear stress increased the expression of an endogenous PXR target gene MDR1, which is a known PXR target encoding p-glycoprotein or ATP-binding cassette B1 (ABCB1), a transporter responsible for drug efflux (12,13). Quantitative reverse-transcriptase PCR (qRT-PCR) showed that MDR1 expression was induced by LSS, but not OSS, in human umbilical vein ECs (HUVECs) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to the small intestinal epithelium, fully differentiated Caco-2 cells form a monolayer of polarized cells, develop tight junctions, and are surmounted by an apical brush border (Hidalgo et al, 1989;Vachon and Beaulieu, 1992). Another inherent property of the Caco-2 cells is the expression of many enterocytic transporter systems, the expression level of which often increases during cell differentiation (Anderle et al, 1998;Siissalo et al, 2007). The passage number (the number of times the cells in the culture have been detached, diluted, and grown again to near confluence) of Caco-2 cells also affects many of their properties, such as cell viability and growth in culture (Briske-Anderson et al, 1997;Anderle et al, 1998).…”
mentioning
confidence: 99%
“…Another inherent property of the Caco-2 cells is the expression of many enterocytic transporter systems, the expression level of which often increases during cell differentiation (Anderle et al, 1998;Siissalo et al, 2007). The passage number (the number of times the cells in the culture have been detached, diluted, and grown again to near confluence) of Caco-2 cells also affects many of their properties, such as cell viability and growth in culture (Briske-Anderson et al, 1997;Anderle et al, 1998). Thus, it is important to know and define the passage number of the cells under investigation, as well as interesting to examine its effect on UGT expression.…”
mentioning
confidence: 99%
“…A pure Caco-2 cell model also has a overexpression of P-glycoprotein which may lead to higher secretion rates and consequently lower permeability in the absorptive direction (Anderle et al 1998 ). The HT-29MTX cell line has less expression of tight junctions.…”
Section: Relevance To the Human In Vivo Situationmentioning
confidence: 99%